Model Of Mental Health Enhancement Based on Stipatthana 4 (4 Foundations of Mindfulness) To Reduce Stress in Living Life of People in Nakhonpathom Province - Phookonglee, Sudjai; Kinasen, Winyu; Wuttiin, Surisa (Journal of Dhamma for Life, 2025)
This study aimed to: 1) examine the fundamental components of mental health promotion based on the Four Foundations of Mindfulness (Satipatthana) to reduce stress, 2) develop a mental health promotion model integrating the Four Foundations of Mindfulness, and 3) implement and test the model in the current context among people in Nakhon Pathom province. A mixed-methods research design was employed. The sample consisted of 400 participants, with an experimental group of 30. Research instruments included questionnaires, in-depth interviews, a stress assessment form, and the RQ mental health assessment. Data were analyzed using second-order confirmatory factor analysis (CFA), frequency, percentage, standard deviation, and Paired Sample t-test. The results revealed that: (1) The model demonstrated a good fit with empirical data. Fit indices met the standard criteria (P = 0.101, Relative X² < 2, SRSEA, RMR, and SRMR < 0.05; GFI, AGFI, NFI, and NNFI > 0.95). (2) The developed model consisted of three key components: “Resilience Power” (building inner strength, calmness, self-control, and confidence to overcome challenges), “Motivation Power” (inspiration from positive perspectives and support from the environment), and “Fighting Power” (mindfulness practice, cognitive reframing, exploring new solutions, goal setting, and evaluation). This model integrated mental health promotion with the Four Foundations of Mindfulness to reduce stress in a structured approach. (3) The experimental results showed a statistically significant reduction in stress and an increase in mental strength after one week of practice. Stress levels decreased from 34.23 to 31.97 (t = 3.77, P < 0.01), while mental health scores increased from 55.37 to 63.60 (t = 10.40, P < 0.01).